Temporal changes in soil properties: Insights from a 37-years-old Swiss soil library - Sarah Semeraro; Roxane Tuchschmid; Jean-Michel Gobat; Sergio Rasmann; Renée-Claire Le Bayon (Geoderma)
Over time, soils undergo qualitative and structural changes under the influence of climate, geomorphic processes, parent material weathering, and vegetation, ultimately developing into unique soil types and profiles. Although these pedological drivers are conserved globally, it remains unclear to what extent different soil profiles undergo similar changes over comparable timespans in various environments. To address this gap, we employed a diachronic approach to investigate temporal changes in soil physicochemical properties across diverse Swiss landscapes. Utilizing a comprehensive soil library initiated in 1982, we analyzed 28 archived and modern soil profiles from natural and semi-natural habitats across the Swiss landscape. Several soil properties across 256 soil horizons, including pH, organic matter content, cation exchange capacity, and carbon-to-nitrogen ratio, were assessed in 2020, and findings were compared with archived data to track changes over up to 37 years. We found that distinct soil types such as Cambisols, Fluvisols, and Gleysols exhibit unique physicochemical characteristics, with notable variations observed in the carbon-to-nitrogen ratio. We also found significant variation in how much the physicochemical properties of soil profiles changed over time, with predictable patterns related to climate. Habitats with warmer temperatures, more solar radiation, and increased humidity were the most susceptible to change. By elucidating how climate influences soil properties, this research contributes to more accurate predictions of climate change impacts on soil organic carbon storage.